Persentase Keberhasilan Persilangan Full Diallel beberapa Genotipe Cabai Rawit (Capsicum frutescens) dan Keragaman Fenotipe Karakter Buahnya - Gusrinaldi Gusrinaldi; Irdha Mirdhayati; Zulfahmi Zulfahmi; Rosmaina Rosmaina (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Genetic expansion of plants can be done by crossing between plant genotypes. This research aims to determine the percentage of successful chili crosses using the full diallel method and determine the level of phenotypic diversity resulting from the crosses. This research used five cayenne pepper genotypes, viz. UIN-041, UIN-048, UIN-050, UIN-062, and UIN-063. The crossing of the five genotypes was carried out using the full diallel method. The parameters observed consisted of the percentage of successful crossing, fruit weight, fruit diameter, fruit length, and number of seeds. The data obtained were subjected to analysis of variance and calculation of the phenotypic diversity coefficient for each character. The results of this study showed that the percentage of successful crossing ranged from 15.00 - 43.30%. The highest value was observed in crossing UIN-041 x UIN-050 and the lowest in UIN-062 x UIN-048. The low successful percentage of crossing is influenced by the pollen condition of the male parents and the level of cross-compatibility. The phenotypic variability value of the fruit weight and fruit length characters was 0.48 and 1.50, respectively, and that was classified as narrow variability, while the fruit diameter and fruit number characters were 5.23 and 120.34, respectively, and classified as broad variability.